Contabilidade para pequenas e médias empresas: uma análise da emissão e adoção da regulação sob a perspectiva da Teoria Tridimensional do Direito - Adriana Giarola Vilamaior (2011)
The quality of financial statements information is crucial in the decision process of general users. So, the IASB has published a unique set of international accounting standards of high quality. In July 2009, the IASB published International Accounting Standard to Small and Medium Enterprises, which was adopted in Brazil in December ofthe same year. Given this scenario, the objective was to identify the values and facts that were present in the adoption of IFRS tor SME from the perspective ofthe Miguel Reale theory. This theory shows that the rule of law arises from the dialectic between a complex set of values and a set of facts thatgive rise to different normative propositions. The agency with regulatory power then edits the norm. To achieve this objective was made a qualitative descriptive research. Data were collected through desk research and interviews. It was analyze Reports on the Observance ofStandards and Codes Accounting and Auditing from 90 countries, I\/Iinutes of the Advisory Board of the IASB, Law Project No. 374-l and Resolution CFC No. 1050 of 2005. The interview was conducted with Teacher Eliseu Martins, he is emeritus teacher at FEA / USP. The complex factual showed that the SME accounting standards had no standards. And it was inadequate. In addition, the complex set of valrrcs was marked by the absence of qualitative characteristics of information. The information was considered unreliable, nontransparent,inaccurate, incomplete, excessive and/or expensive. The resorrrce also showed that the expectation of the set of Iacts should be marked mainly by aid in achieving global financial stability. For the complex of values obtained with the adoption of standards lor SMEs will be marked by information that has IASB quality characteristics. The inquiry demonstrated that possible obstacles to the adoption of standard difficulty are in enforcement and informal enterprises.